Reconceptualising Shareholder Remedies to Mitigate the Problems Caused by the Overlap between Section 994 and Part 11 Companies Act 2006 - Shenara Perera (UCL Journal of Law and Jurisprudence, 2019)
To download this paper, please click here. The contemporary paradigm relating to shareholder remedies under English company law identifies a fundamental overlap between the Section 994 and Part 11 of the Companies Act 2006. The underlying cause of the overlap is that an alleged breach of directors’ duties can establish a claim under both remedial jurisdictions. This article argues the overlap between the jurisdictions generates three undesirable consequences. First, shareholders have used s.994 to obtain personal relief on a corporate claim, as opposed to pursuing a derivative claim for corporate relief. Second, s.994 has been used to obtain corporate relief on a corporate claim, instead of bringing a derivative claim. Third, shareholders can exploit s.994 to obtain an order authorising a derivative claim, effectively circumventing the threshold test in Pt 11. The article explores the undesirable impact of these consequences for English company law. In each case, the article recommends three reform proposals which, if implemented, would reconceptualise shareholder remedies under English company law and mitigate the problems caused by the overlap between s.994 and Pt 11.